2016
DOI: 10.1016/j.saa.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, Hirshfeld surfaces and DFT computation of NLO active (2E)-2-(ethoxycarbonyl)-3-[(1-methoxy-1-oxo-3-phenylpropan-2-yl)amino] prop-2-enoic acid

Abstract: Nonlinear optical (NLO) activity of the compound (2E)-2-(ethoxycarbonyl)-3-[(1-methoxy-1-oxo-3-phenylpropan-2-yl)amino] prop-2-enoic acid is investigated experimentally and theoretically using X-ray crystallography and quantum chemical calculations. The NLO activity is confirmed by both powder Second Harmonic Generation (SHG) experiment and first hyper polarizability calculation. The title compound displays 8 fold excess of SHG activity when compared with the standard compound KDP. The gas phase geometry optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(115 citation statements)
references
References 47 publications
0
114
0
Order By: Relevance
“…In the HS plotted over d norm (Fig. 4), the white surface indicates contacts with distances equal to the sum of van der Waals radii, and the red and blue colours indicate distances shorter (in close contact) or longer (distinct contact) than the van der Waals radii (Venkatesan et al, 2016). The bright-red spots appearing near O1 and hydrogen atom H15 indicate their roles as the respective donors and/or acceptors; they also appear as blue and red regions corresponding to positive and negative potentials on the HS mapped over electrostatic potential (Spackman et al, 2008;Jayatilaka et al, 2005) as shown in Fig.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…In the HS plotted over d norm (Fig. 4), the white surface indicates contacts with distances equal to the sum of van der Waals radii, and the red and blue colours indicate distances shorter (in close contact) or longer (distinct contact) than the van der Waals radii (Venkatesan et al, 2016). The bright-red spots appearing near O1 and hydrogen atom H15 indicate their roles as the respective donors and/or acceptors; they also appear as blue and red regions corresponding to positive and negative potentials on the HS mapped over electrostatic potential (Spackman et al, 2008;Jayatilaka et al, 2005) as shown in Fig.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…In the HS plotted over d norm (Fig. 5), the white surface indicates contacts with distances equal to the sum of van der Waals radii, and the red and blue colours indicate distances shorter (in close contact) or longer (distant contact) than the van der Waals radii, respectively (Venkatesan et al, 2016). The bright-red spots appearing near O1 and hydrogen atoms H5, H2A, H8B indicate their roles as donors and/or acceptors; they also appear as blue and red regions corresponding to positive and negative potentials on the HS mapped over electrostatic potential (Spackman et al, 2008;Jayatilaka et al, 2005) shown in Fig.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…The absorption band at 1419 cm −1 is attributed to the C=C and C-C stretching modes of the 5-methylbenzimidazole ring [21]. The weak bands at 1295 and 813 cm −1 are attributed to the ν(C-N aromatic ) and δ(C-H) modes [22].…”
Section: Ir Spectrum Of (C8h9n2)3[al(c2o4)3]•3h2omentioning
confidence: 99%